2019
DOI: 10.3390/w11050997
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Hydrological Effects of Bioretention Cells for Urban Stormwater Runoff in Response to Climatic Changes

Abstract: An investigation into the effectiveness of bioretention cells (BCs) under potential climatic changes was conducted using representative concentration pathways. A case study of Guangzhou showed changes in peak runoff in climate change scenarios, with obvious growth in RCP8.5 and slight growth in RCP2.6. The performance of BCs on multiple parameters, including reduction of runoff volume, peak runoff, and first flush, were examined in different design storms using a hydrology model (SWMM). The effectiveness of BC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 55 publications
3
9
0
Order By: Relevance
“…The runoff control rate greatly reduced because the temporary water depth rise rate on the surface of the bioretention system increases with the increase of the rainfall intensity, resulting in a rapid shortening of the overflow start time and a large increase in the overflow, lead to increase in the proportion of overflow in the total amount of runoff, and the runoff control rate is reduced. The runoff reduction rate increased slightly with the increase of rainfall intensity, which is consistent with the previous studies [29,30]. However, the reduction of runoff in the whole bioretention system was limited, and the runoff reduction rate of the three systems A1, A2, and A3 varied between 17.8% and 30.9%.…”
Section: Water Quality Analysissupporting
confidence: 90%
“…The runoff control rate greatly reduced because the temporary water depth rise rate on the surface of the bioretention system increases with the increase of the rainfall intensity, resulting in a rapid shortening of the overflow start time and a large increase in the overflow, lead to increase in the proportion of overflow in the total amount of runoff, and the runoff control rate is reduced. The runoff reduction rate increased slightly with the increase of rainfall intensity, which is consistent with the previous studies [29,30]. However, the reduction of runoff in the whole bioretention system was limited, and the runoff reduction rate of the three systems A1, A2, and A3 varied between 17.8% and 30.9%.…”
Section: Water Quality Analysissupporting
confidence: 90%
“…It means the rain garden could not process the rainfall with long duration. Similarly, other researches [27,50] found a similar result. Wang et al [27] found that there is an obvious decrease in effectiveness under longer return period (e.g., 100 years) events compared to the simulated runoff reduction for 1 year, 1 h storms.…”
Section: Performance Of Rain Gardensupporting
confidence: 80%
“…Similarly, other researches [27,50] found a similar result. Wang et al [27] found that there is an obvious decrease in effectiveness under longer return period (e.g., 100 years) events compared to the simulated runoff reduction for 1 year, 1 h storms. The research of Wang et al [50] also shows that when the intensity of climate increased, LIDs were not very helpful.…”
Section: Performance Of Rain Gardensupporting
confidence: 80%
“…Several studies recognize the sensitivity of LID modeling to LID scale and distribution (Wolfand et al 2018; Wang et al 2019), to rainfall event size and duration (Qin et al 2013; Fry and Maxwell 2017; Mao et al 2017), and to physical LID parameters such as hydraulic conductivity or soil thickness (Gülbaz and Kazezyılmaz‐Alhan 2017; Gao et al 2018). However, model sensitivity to other siting and routing parameters such as outflow routed from LID, LID placement with adjusted imperviousness, and the percent of impervious area runoff treated by LID is not well studied.…”
Section: Introductionmentioning
confidence: 99%